2020
DOI: 10.1186/s12896-020-00657-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined pretreatment of sugarcane bagasse using alkali and ionic liquid to increase hemicellulose content and xylanase production

Abstract: Background Lignin in sugarcane bagasse (SB) hinders its utilization by microorganism, therefore, pretreatment methods are employed to make fermentable components accessible to the microbes. Multivariate analysis of different chemical pretreatment methods can aid to select the most appropriate strategy to valorize a particular biomass. Results Amongst methods tested, the pretreatment by using sodium hydroxide in combination with methyltrioctylammoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…As the source of enzyme also affects the efficiency of hydrolysis, considerations were therefore given to the producing strains. B. borstelensis UE10 and B. borstelensis UE27 and A. thermoaerophilus UE1 were previously reported to produce thermostable cellulase by fermenting an agro-industrial waste product, SB ( Ejaz et al, 2020a ), whereas B. aestuarii UE25 was reported to produce cellulase ( Ejaz et al, 2019 ) and xylanase ( Rashid et al, 2020 ) by fermenting alkali- and ionic liquid-pretreated SB. In the present study, except for B. vallismortis MH 1, all the strains produced variable titers of multiple hydrolytic enzymes ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the source of enzyme also affects the efficiency of hydrolysis, considerations were therefore given to the producing strains. B. borstelensis UE10 and B. borstelensis UE27 and A. thermoaerophilus UE1 were previously reported to produce thermostable cellulase by fermenting an agro-industrial waste product, SB ( Ejaz et al, 2020a ), whereas B. aestuarii UE25 was reported to produce cellulase ( Ejaz et al, 2019 ) and xylanase ( Rashid et al, 2020 ) by fermenting alkali- and ionic liquid-pretreated SB. In the present study, except for B. vallismortis MH 1, all the strains produced variable titers of multiple hydrolytic enzymes ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Aneurinibacillus thermoaerophilus strain WBS2 was reported as a motile, rod-shaped, aerobic, thermophilic bacterium isolated from the hot spring of India ( Acharya and Chaudhary, 2012 ), whereas A. thermoaerophilus UE1 was isolated from soil in Pakistan which was reported to produce thermostable cellulase by fermenting sugarcane bagasse (SB; Ejaz et al, 2020a ). Another bacterial species, Brevibacillus borstelensis , has been reported for various enzymatic activities including xylanase ( Kamsani et al, 2015 ), amylase ( Awasthi et al, 2018 ), lipase ( Tsai et al, 2007 ), and cellulase by fermenting SB which was isolated from a crocodile pond in Manghopir, Pakistan ( Ejaz et al, 2020a ), whereas Bacillus aestuarii UE25 was reported to produce xylanase ( Rashid et al, 2020 ) and cellulase ( Ejaz et al, 2019 ) by fermenting alkali and ionic liquid-pretreated SB.…”
Section: Introductionmentioning
confidence: 99%
“…Hemicellulose extraction involves various pretreatments, which ease the subsequent XOS producing steps. At present, the main methods for pretreatment include: heat-dilute-acide hydrolysis (Liu et al, 2012), organic solvent extraction (Zhang et al, 2016), pyrohydrolysis of hemicellulose (Zhao et al, 2019) and alkaline extraction (Rashid et al, 2020). Compared to other pretreatment methods, alkaline extraction operating conditions are less demanding (lower temperature and pressure) (Badiei et al, 2014) and promote the dissolution of lignin and also protect cellulose from drastic degradation (Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Associations among lignin, cellulose, and hemicelluloses along with crystallinity hinder the utilization of SB and other plant materials in fermentation processes. So the substrate is subjected to pretreatment methods to get over the hindrance and increase the availability of constituents of biomass to the respective enzymes that can ultimately increase the yield of reducing sugars and other products [5]. Amongst many chemical pretreatment agents, ionic liquids (ILs) have emerged as potential solvents for dissolving lignocellulosic (LC) biomass.…”
mentioning
confidence: 99%
“…Combining the advantages of SSF processes, the novelty of IL pretreatment, and the cultivation of thermophilic bacteria under SSF, this study was designed to obtain multienzyme preparation from Bacillus aestuarii UE25. The organism was isolated from a crocodile pond and has been reported for the production of thermostable cellulase [7] and xylanase [5]. However, it has not been utilized for the production of multienzyme preparation under SSF processes.…”
mentioning
confidence: 99%